ANALISIS PENGUNGKAPAN SUSTAINABILITY REPORT BERDASARKAN GRI STANDARDS PADA PT. BANK CENTRAL ASIA, TBK DAN PT. BANK MANDIRI (PERSERO), TBK (STUDI KASUS PADA BURSA EFEK INDONESIA) - Lusia Rechylia Luga; Wilhelmina Mitan; Wihelmina Maryetha Yulia Jaeng (Universitas Nusa Nipa Maumere, 2025)
This study aims to analyse the disclosure and compliance level of Sustainability Reporting based on the GRI Standards 2021 at PT. Bank Central Asia, Tbk and PT Bank Mandiri (Persero), Tbk for the 2023 period. The research employs a qualitative descriptive methodology Data collection methods unlized in this study include documentation analysis, literature review, and internet research. The data analysis techniques consist of content analysis and comparative methods. The findings indicate that both banks have disclosed sustainability information in accordance with the GRI Standards, albeit with varying degrees of completeness and detail PT Bank Mandiri (Persero), Tbk demonstrates a more comprehensive level of disclosure that is better aligned with GRI standards compared to PT. Bank Central Asia, Tbk, particularly in specific disclosures. Regarding compliance levels, PT. Bank Central Asia, Tbk achieved 100% compliance with general disclosures in its Sustainability Report, classified as